Alcohol Consumption among University Students in Iceland: Effects of Peer Influence on Hazardous Alcohol Use - Thelma Gunnarsdóttir 1994- (2018)
Harmful use of alcohol is one of the leading causes of death and disability worldwide. One group that is particularly at risk for the negative consequences of alcohol is the college population, where risky alcohol consumption is common. This study examined alcohol consumption among university students in Icelandic and the effects of peer influence on alcohol use among male and female students. Altogether, a sample of 712 participants (412 university students and 300 non-university peers) completed an online survey that included the Alcohol Use Disorder Test (AUDIT) and an 11-item scale which assessed perceived peer influence regarding alcohol use. The results provided support for the primary hypothesis; university students drank more alcohol on average than their non-university peers. Contrary to the secondary hypotheses, findings indicated that female students perceived more peer influence than male students and a negative relationship existed between perceived peer influence and level of alcohol use. Lastly, male and female students were equally as likely to meet the criteria of showing hazardous alcohol consumption. In conclusion, findings of the current study provide important evidence about drinking behavior of university students in Iceland. Further research is needed in a sample that better represents the population of university students to draw a more definitive conclusion. Keywords: AUDIT, peer influence, university students, hazardous alcohol use Skaðleg neysla áfengis er talin vera ein helsta orsök dauðsfalla og örorku um allan heim. Háskólanemar eru meðal þeirra sem einna helst eru taldir útsettir fyrir neikvæðum afleiðingum áfengisneyslu en óhófleg neysla er algeng hjá þeim hópi. Markmið þessarar rannsóknar var að kanna áfengisneyslu háskólanema á Íslandi ásamt því að skoða hvort jafningjaáhrif séu einn þeirra þátta sem ýta undir óhóflega áfengisneyslu hjá karl- og kvenkyns nemendum. Alls svöruðu 712 einstaklingar (412 háskólanemar og 300 jafningjar sem ekki stunda nám) rafrænum spurningalista ...